دور السياحة في تحسين واقع المجتمعات الريفية - هرمز, نور الدين; أبا زيد, ثناء; اسبر, ميساء (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول هذا البحث أهمية الأنشطة غير الزراعية وخاصةً السياحة في تحسين واقع المجتمعات الريفية عبر تحسين مستوى معيشة سكانها، ومن خلال زيادة وتنويع مصادر الدخل وزيادة فرص العمل وتخفيض معدلات الفقر، وذلك عبر مجموعة من الأمور خاصة بالسياحة. وقد توصل البحث من خلال اختبار الفرضيات إلى أن الأسر التي تجمع بين العمل السياحي والزراعي تحصل على متوسط دخل أعلى ولديها قدرة اكبر على الانفاق على الطعام وغير الطعام وتحمل النفقات المختلفة مقارنة بالأسر الأخرى التي تعمل في الزراعة فقط. This research deals with the importance of non-agricultural activities, especially tourism, in improving the status of rural communities by improving their standard of living, increasing and diversifying their incomes, and reducing poverty rates. By testing these hypotheses, this study shows that households combining agriculture and tourism obtain a higher income average, have a greater capacity of spending on food and non-food, compared with other families that only do agricultural activities.